2019
DOI: 10.4314/gjpas.v25i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Helicobacter pylori</i> infection among dyspepsia patients in Calabar

Abstract: Helicobacter pylori is an ubiquitous organism. It is estimated that more than 50% of the world’s population is infected with the bacteria. The infection is typically acquired in infancy and has been associated with poor living conditions and low socio-economic status. Once helicobacter pylori is acquired, it commonly persists lifelong unless treated. This pathogen has been implicated as a major aetiologic agent in the pathogenesis of peptic ulcer disease and is an established carcinogen. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A prevalence rate of 40.6% for H.pylori infection was found in our study. This is similar to the prevalence of H. pylori in a similar study of 42.6% by Mbang et al in Calabar 11 but lower than the reported rates by Adeniyi et al in Ibadan 27 , Ezugwu in Awka 28 , Ishaleku in Ke 29 , and Bello et al in Kano 30 . Archampong et al also found a higher prevalence rate of 74.5% in a similar study in Ghana 31 whereas Jemikaleja found a much lower prevalence rate of 12.…”
Section: Medical Co-morbidities In the Subjectssupporting
confidence: 89%
See 1 more Smart Citation
“…A prevalence rate of 40.6% for H.pylori infection was found in our study. This is similar to the prevalence of H. pylori in a similar study of 42.6% by Mbang et al in Calabar 11 but lower than the reported rates by Adeniyi et al in Ibadan 27 , Ezugwu in Awka 28 , Ishaleku in Ke 29 , and Bello et al in Kano 30 . Archampong et al also found a higher prevalence rate of 74.5% in a similar study in Ghana 31 whereas Jemikaleja found a much lower prevalence rate of 12.…”
Section: Medical Co-morbidities In the Subjectssupporting
confidence: 89%
“…This nding is similar to the report by Khaled et al 12 in their retrospective study of outpatients with dyspepsia using endoscopic procedure at Grady Memorial Hospital in Atlanta, Georgia, USA. Kooffreh-Ada et al in Calabar 11 ,Nigeria reported no sex predilection while Ahmed et al 10 in Egypt reported slightly higher prevalence in males. Explanations for the higher prevalence in females in this study may include hormonal differences between males and females, and, higher health seeking behaviors in females as well as higher prevalence of functional gastrointestinal disorders in females.…”
Section: Medical Co-morbidities In the Subjectsmentioning
confidence: 93%
“…Individuals with habits of smoking and use of alcohol are at greater risk of gastric cancer, while those who consume vegetables, fruits, and vitamins were reported to have an inverse association with gastric cancer [49,50]. Various studies have reported that HPIs are acquired during early childhood, but the symptoms may linger or manifest between the ages of 41-60 years, which is the age range mostly having the highest prevalence [28,51].…”
Section: Epidemiology Of Hpimentioning
confidence: 99%
“…This suggests that regardless of education level, disregarding proper hygiene can increase the risk of infection. However, other studies by Mbang et al [23] and Okoroiwu et al [24] reported a high prevalence of H. pylori among individuals with a tertiary level of education or those belonging to the literate class, possibly because they assume immunity and overlook simple hygiene procedures for handling vegetables.…”
Section: Discussionmentioning
confidence: 92%